1995
DOI: 10.4141/cjps95-024
|View full text |Cite
|
Sign up to set email alerts
|

Differences among orchardgrass cultivars in response to hay and rotational grazing management

Abstract: This study was conducted to compare orchardgrass (Dactylis glomerata L.) cultivar performance under contrasting management systems (hay vs. rotational grazing) during the first two production years. The trial consisted of eight orchardgrass cultivars broadcast seeded in a randomized complete-block design, with three replications. The perimeter of each replication was fenced, and the area was divided into two sections. The first section was managed as a simulated hay production system. The second section was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 8 publications
3
11
0
Order By: Relevance
“…The results of these experiments give further support to earlier findings (Papadopoulos et al 1995) that assessing the performance of OG cultivars under a hay management system was not effective in determining their performance under grazing. A mineral supplement containing Cu, among other traces, would be required of ruminants consuming pure stands of OG.…”
Section: Papadopoulos Et Al -Nutritional Quality Of Orchardgrass 599supporting
confidence: 81%
See 2 more Smart Citations
“…The results of these experiments give further support to earlier findings (Papadopoulos et al 1995) that assessing the performance of OG cultivars under a hay management system was not effective in determining their performance under grazing. A mineral supplement containing Cu, among other traces, would be required of ruminants consuming pure stands of OG.…”
Section: Papadopoulos Et Al -Nutritional Quality Of Orchardgrass 599supporting
confidence: 81%
“…This enhanced quality can be attributed to changes in the canopy structure resulting from frequent defoliation under rotational grazing (Papadopoulos et al 1995). Herbage CP content of cultivars did not appear to be influenced by DM yield under both management systems (Papadopoulos et al 1995).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, progress achieved by breeding orchardgrass for superior adaptation and agronomic performance under hay management may not necessarily be realized under grazing management. Different management practices, such as hay vs. management intensive rotational grazing (MIRG), can alter sward traits such as crop growth rate, tiller density, or leaf area index, drastically altering the ranking of cultivars for production traits such as forage yield (Papadopolous et al 1995). These authors concluded that orchardgrass cultivars differed in their adaptation to MIRG and that this information could not be predicted from cutting trials.…”
mentioning
confidence: 99%
“…), timothy (Phleum pratense L.), and reed canarygrass (Phalaris arundinacea L.) have shown satisfactory to excellent adaptation to a wide range of soil types and conditions associated with beef production in Atlantic Canada (Bates et al 1979;McKenzie and Connolly 1991a, b;Papadopoulos et al 1995;Kunelius et al 2003). These six pasture species are well-suited to the Atlantic region's climate since they require cooler soil and air temperatures than southern species for optimum growth (Blaser et al 1952).…”
mentioning
confidence: 99%